Bio-indicator species and Central African rain forest refuges in the Campo-Ma'an area, Cameroon - Tchouto, M. G. P.; de Wilde, J. J. F. E.; de Boer, W. F.; van der Maesen, L. J. G.; Cleef, A. M. (Systematics and biodiversity, 2009)
This study aims to examine the geographical position of late Pleistocene forest refuges in the tropical lowland rain forest in southern Cameroon by analysing the distribution of 178 selected bio-indicator species. We studied the distribution patterns of these species, such as strict and narrow endemics, as well as a number of well-known slow dispersal species, to test whether the entire Campo-Ma'an rain forest was part of a late Pleistocene rain forest refuge. Special attention was given to taxa with slow dispersal abilities such as those within Begonia sect. Loasibegonia and sect. Scutobegonia, Rinorea spp., Caesalpinioideae and Rubiaceae. Species that occur in other rain forest refuges and that reach their northern limit of distribution in the Campo-Ma'an area were also included in the analysis. The distribution patterns of the 178 bio-indicator species were displayed in several maps. There was a high concentration of bio-indicator species in the lowland evergreen forest rich in Caesalpinioideae, and in the submontane forests in the National Park and in the Kribi-Campo-Mvini area, and a relatively low concentration of these species in the Ma'an area. Similar patterns were observed for the distribution of strict and narrow endemic species, Begonia, Caesalpinioideae and Rubiaceae. Most of these species were particularly frequent on higher altitudes in the lowland rain forests, especially along the upper slopes of hills near the top, or along riverbanks. There was a relatively even distribution of bio-indicator species from the Rubiaceae family within the Campo-Ma'an area. The distribution of Begonia showed that some species were frequent in mountainous areas, along slopes near hilltops in the lowland forest and others were located along small streams in the lowland forest. As for the Caesalps, their distribution showed a high concentration of species in the evergreen forest rich in Caesalpinioideae with a decrease in number in the coastal forest and the mixed evergreen and semi-deciduous forest. As for the Rinorea, many indicator species were mostly confined to the lowland forest, particularly in the evergreen forest rich in Caesalpinioideae. These species distribution patterns corroborate the view of many authors who argue that during glacial times forests were restricted to the upper slopes of hills, upper altitudinal zones in the lowland forests, or along riverbanks. Our findings, therefore, suggest that the Campo-Ma'an area falls within a series of postulated rain forest refuges in Central Africa as proposed by previous authors.